Gender earnings ratio differences among population groups in Canada - Aneta Bonikowska (Economic and Social Reports)
This study explores differences in mean annual earnings from paid employment between women and men within 11 population groups in Canada. Substantial differences were found in the gender earnings ratio within different population groups. The highest earnings ratio was observed among Black workers, where Black men had the lowest mean earnings of men in the 11 groups. The lowest earnings ratio was among Japanese workers, where men of Japanese origin had the highest mean annual earnings of all groups, surpassing those of White men. Differences in weekly hours worked and sector of employment explained substantial shares of the earnings differences between women and men in all population groups. Differences in occupational distribution further explained some of the gender earnings gaps for many groups. While the overall gender earnings ratio increased in Canada from 1996 to 2016, these gains were not distributed evenly across population groups. Southeast Asian and White women saw the biggest increases in their earnings relative to men in their population groups. There was essentially no change among Black and South Asian workers, and small declines were seen in the gender earnings ratio among Japanese, Latin American, and Arab and West Asian employees.